Neurologic Characterization of Craniosynostosis: Can Direct Brain Recordings Predict Language Development?. Issue 1 (January 2021) - Wu, Robin; Nie, James; Abraham, Paul; Halligan, Taylor; Gabrick, Kyle; Peck, Connor J.; Sawh-Martinez, Rajendra; Steinbacher, Derek M.; Alperovich, Michael; McPartland, James; Persing, John A.
Abstract : Purpose: Nonsyndromic craniosynostosis (NSC) is associated with language deficits. Conventional tests, such as the Bayley Scales of Infant Development (BSID), may not reflect accurate long-term cognition. Alternatively, mismatch negativity (MMN) waves recorded via electroencephalogram (EEG) measure neural responses to speech and may objectively predict language development. This study aimed to (1) correlate infant MMN to future language achievement and (2) compare MMN among subtypes of NSC. Methods: Pre and postoperatively (mean operative age 9.5 months), NSC participants received the BSID and EEG phoneme-discrimination paradigm(80 dB, 250 Hz). The MMN was the largest negative amplitude in the difference wave 80 to 300 ms after stimuli. To measure cognitive outcome, patients completed a neurodevelopmental battery (Wechsler-Abbreviated Scale of Intelligence and Wechsler-Fundamentals) at >6 years of age. Results: Eleven NSC patients with EEG testing in infancy were neurocognitively tested (average age 8.0 years; 27% female; 55% sagittal, 27% metopic, 9% unicoronal, 9% sagittal/metopic). The left frontal cluster MMN strongly correlated with word-reading ( r  = 0.713, P  = 0.031), reading-comprehension ( r  = 0.745, P  = 0.021), and language-composites ( r  = 0.0771, P  = 0.015). Conversely, BSID scores did not yield significant predictive value ( r  < 0.5, P  > 0.05). Follow-up event related potentials (ERP) comparison included 39 normal control, 18 sagittal, 17 metopic, 6 unilateral-coronal infants. Preoperatively, sagittal ( P  = 0.003) and metopic ( P  = 0.003) patients had attenuated left frontal MMN compared to controls. Postoperatively, the sagittal cohort was normalized to controls while metopic patients retained attenuations ( P  = 0.041). Conclusion: ERP assessment in NSC had significantly better predictive value for future neurocognition than the BSID. Preoperatively, sagittal and metopic patients had attenuated neural response to language; postoperatively, sagittal patients had improved responses in comparison to metopic patients. Use of ERP assessment may help tailor treatment for language deficits earlier in development. Abstract : Supplemental Digital Content is available in the text